MEANING AND OBJECTIVES OF THE ACTIVITIES OF HUMANITARIAN ORGANIZATIONS (Bulletin of criminological association of Ukraine, 2024)
The article emphasizes that the significance of the activities of humanitarian organizations lies in implementing a wide range of measures to assist humanity in situations that have extremely destructive consequences for the life and health of people, their honor and dignity, environmental protection, and the well-being of both individual families and these societies in the long term, which are carried out in close cooperation with public authorities and are not associated with any institutional or organizational barriers that are characteristic of public administration, are based on the basic principles of humanitarian policy in a specific country in the world that has suffered a humanitarian disaster, and on the appropriate administrative and legal support that determines the peculiarities of the functioning of public authorities in those regions or settlements on the territory of which humanitarian operations are directly carried out. It is stated that the tasks of humanitarian organizations include training in first aid skills, which is of particular importance among employees of the National Police of Ukraine, the State Emergency Service of Ukraine, volunteers, cadets of higher education institutions with specific training conditions who are directly involved in providing assistance to the population during rocket attacks on the civilian population, as well as other natural and man-made disasters; responding to emergencies, based on coordinated interaction of humanitarian organizations with local government bodies (municipal services), bodies and units of the National Police of Ukraine, units of the State Emergency Service of Ukraine, other services and volunteer organizations that immediately arrive at the scene; ensuring the functioning of mobile medical teams of the Ukrainian Red Cross, the international organization "Doctors without Borders" and the International Medical Corps.
Keywords: humanitarian organizations; meaning; tasks; humanitarian policy; administrative and legal support; first aid; mobile medical teams